STUDI KASUS BIMBINGAN DAN KONSELING BAGI ANAK PUTUS SEKOLAH PADA PENDIDIKAN KESETARAAN - Eka Pasca Bayu Surya; Neviyarni Neviyarni (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2020)
The implementation of equality education is now at a stage where this education is an alternative education that can be used to develop access to education. Changes that occur in students who at first most of the school age change to school age. The implementation of this education consists of Package A, Package B, and Package C, one of which is held by the Love Bundo Bukittinggi City Community Learning Activity Center (PKBM). The background to the occurrence of dropouts at this time is generally dominated by disciplinary problems that are deemed failing to be obeyed by students. This eventually reached a turning point that made them aware of returning to school. Unfortunately, equality education has not been facilitated with real counseling guidance services. For now guidance and counseling services are taken over by all subject teachers. The study was conducted in a descriptive qualitative manner by describing what information was in accordance with the phenomenon that occurred. Data were analyzed by stages of reduction, presentation, drawing conclusions and data verification. The field of service development is focused on learning, social, personal and career. Service delivery is more inclined in the form of motivation and enthusiasm to persist in continuing to complete education, experience is a valuable lesson so that it does not recur. Based on the results of the study note that teachers use Eclectic Counseling and specifically some cases use Home Room Program techniques. The results shown by this activity are prioritized towards changing attitudes and behavior of students to be able to return to formal education.Keywords: Counseling guidance services, Dropouts, Equality Education